Correction: An integrated surgical training program for hepatic cystic echinococcosis in Xinjiang of China. - Hongwei Zhang; Jian Yang; Jiang Li; Jing Yang; Yunbao Yu; Guisheng Liu; Yongguo Zhang; Long Zhang; Wei Guo; Abuduwayiti; Hong Sun; Shuxia Guo; et al. (Public Library of Science (PLoS), 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0008023.].